(untitled) (The Pretoria Student Law Review, 2021)
In the editors’ note to the inaugural edition of the Pretoria Student Law Revie (PSLR) the editors wrote that the purpose of the PSLR is to serve as a platform for students to engage in ‘academic legal writing’. To students interested in publishing in the PSLR, or any other law journal for that matter this might raise the questions: ‘What is academic legal writing?’; ‘Are there other forms of legal writing?’; and ‘If so, how are they different from academic legal writing?’ These are important questions. They certainly do not only arise for potential student authors for the PSLR, but all law students who at some stage of their studies have to write ‘academic’ essays or dissertations, somehow different from ‘practical’ exam and test answers or pleadings for moot courts, or pretend-contracts. They also confront legal academics on a daily basis when they think about the nature and purpose of their work. I attempt here some answers to them.